Ethnomathscience identification of traditional weapons of sigi biromaru - Wahyuni H Mailili; Gustina; Yuli Nurmayanti; Irmawati (Balai Diklat Keagamaan Ambon, 2023)
This descriptive research uses an ethnographic approach to identify ethnomascience on parts of Sigi Biromaru's traditional weapons that can be used as media and innovation in learning mathematics and science/IPA. The results of literature reviews show that concepts in the fields of mathematics, and science/IPA are found in parts of the traditional weapon described in the descriptions of the table. The results of the research show that the Kaliavo, Guma, and Doke shapes include triangular, square-long, quadrilateral, horizontal, hexadecimal, symmetrical, structural, quadrillary, and straight lines. On the other hand, physical concepts such as momentum, implosive, style, pressure, cultivation, tree morphology biology, tree anatomy, forest ecology, roles and cycles of carbon, forestry, plants, ecosystems, and human interaction with its natural environment, human development, ecological, technological, and cultural. Then ideas about chemistry, such as solid substances, and chemical elements of iron and steel.